Affective Communication in Feminism: The Lived Experience of Highly-Educated Generation Z Women in Hulu Sungai Tengah Regency, Indonesia - Siti Nor Khadijah; Muhammad Alif (International Journal of Science and Environment (IJSE), 2026)
This study examines how highly educated Generation Z women in Hulu Sungai Tengah Regency, South Kalimantan, Indonesia, use affective communication as a form of everyday feminist practice. Drawing on a qualitative phenomenological design informed by feminist methodology, in-depth interviews were conducted with five key informants and four supporting informants selected purposively. Data were analyzed thematically through transcription, reduction, coding, textural description, interpretation, and researcher reflexivity, and validated through method and source triangulation. The findings show that within a strongly patriarchal and Banjar cultural context that values politeness, religiosity, and social harmony, educated women rarely resist gender inequality through open confrontation. Instead, they rely on empathetic, warm, and relationally sensitive communication to voice disagreement, negotiate identity, and claim recognition without threatening social harmony. Six major patterns emerged: persistent gender stereotyping of educated women, negotiation between traditional and modern values, strategies for voicing the self, the critical function of higher education, symbolic power relations in communication, and ambivalent societal perceptions of educated women. These patterns are explained through Feminist Standpoint Theory, which frames women's lived experience as a legitimate epistemic standpoint, and Affection Exchange Theory, which frames affection as an adaptive relational strategy. The study concludes that affective communication functions as a subtle but meaningful form of everyday feminism, allowing women to defend their dignity and pursue equality while remaining embedded in local cultural norms.